Formation and Electrochemical Behaviour of 1,10-Orthophenanthroline-Co(II) Complex - MODARRES-TEHRANI, Z.; SHAHINI, M.; MOFIDI, J. (Asian Journal of Chemistry, 2010)
By studying cyclic voltammetry, it is established that Co2+ forms a complex with ligand 1,10-orthophenanthroline. The voltamogram of formed complex, [Co(Ph)3]2+, presents three quaisi-reversible systems. Coulometric studies at constant peak potentials show that n = 1 for every system.